SINGLE PARENT: IMPLIKASINYA TERHADAP PRESTASI BELAJAR ANAK - Irma Nuryani Inaku; Muhammad Arif (Irfani, 2021)
This article aims to uncover the problem of single parents or with the term "Single Parent" which has implications for children's learning achievement, namely how the parenting of single parent students in MTs al-Khairat Gorontalo City. Research using qualitative methods. The findings of the research show that the parenting style of single parent students of MTs al-Khairat Gorontalo City is democratic, authoritarian and permissive parenting. Parenting parenting single parent based on the results of the study found that democratic parenting is better implemented. Furthermore, the implication of parenting single parent parenting on the learning achievement of students of MTs al-Khairat Gorontalo City, namely democratic parenting is in the very good category. While authoritarian parenting student achievement is in the good category. Besides that, permissive parenting, learning achievement is good and good enough and student self-development is lacking. The obstacles in parenting single parent are First, Lack of maturity of single parent parenting due to early marriage; Second, is the level of parental education; Third, parental socioeconomic status; Fourth, stress is the result of the status of single parent mother; and Fifth, lack of attention in family education.